Anti-Aging Activity Test and Physical Stability Evaluation of NanoCream Containing Ethanolic Extract of Binara Herb (Artemisia vulgaris L.) - Romauli Anna Marbun; *, Yanna Rotua Sihombing; Ratih Anggraeni (Jurnal FARMASIMED (JFM), 2026)
Background: Antioxidants are compounds that neutralize free radicals or prevent their formation by slowing oxidative reactions, thereby helping to inhibit premature skin aging. Binara herb (Artemisia vulgaris L.) is one of the plants with potential antioxidant properties. Previous studies have shown that binara herb contains flavonoids and exhibits moderate to strong antioxidant activity. Objective: This study aimed to formulate a stable and effective nanoCream  preparation containing binara herb extract (Artemisia vulgaris L.) as an anti-aging agent. Methods: This study employed an experimental research design. The pH test results met the acceptable range (4.5–7), and the viscosity test results complied with the required standard (2,000–5,000 cps). Results: The ethanolic extract of binara herb (Artemisia vulgaris L.) demonstrated very strong antioxidant activity with an IC₅₀ value of 40.36 ± 1.21 µg/mL. The nanoCream  formulation showed good physical stability during storage, as indicated by stable organoleptic characteristics, pH values within the skin-compatible range (6.6–6.8), and viscosity increasing with higher extract concentrations. The irritation test revealed that the 10% nanoCream  formulation was safe and did not cause irritation in volunteers. These findings indicate that the nanoCream  containing ethanolic extract of binara herb has potential for development as a herbal-based anti-aging preparation. Conclusion: The ethanol extract of binara herb showed very strong antioxidant activity (IC₅₀ 40.36 ± 1.21 µg/mL). The formulated nanoCream  was physically stable, had a skin-compatible pH (6.6–6.8), showed increased viscosity with higher extract concentrations, and caused no irritation up to a 10% concentration. Therefore, this nanoCream  has potential as a stable, safe, and effective herbal anti-aging formulation.